Students’ cross-domain mindset profiles and academic achievement in Finnish lower-secondary education - Laurell, Jenni; Puusepp, Ita; Hakkarainen, Kai; Tirri, Kirsi (Frontiers in Psychology, 2025)
IntroductionThis study uses a person-centered approach to explore Finnish lower-secondary school students’ (N = 1106) mindsets across intelligence, giftedness, and creativity. It further investigates the relationship between mindsets profiles, school achievement in various subjects, and gender differences, aiming to address the domain-specificity of the three ability domains.MethodsA self-reported questionnaire was used to measure students’ mindsets, with latent profile analysis (LPA) identifying distinct profiles. School achievement was assessed through academic grades in core and arts subjects, while gender differences in profile membership were examined via logistic regression.ResultsFour mindset profiles emerged: Growth, Fixed, Mixed, and Opposing. Most students exhibited consistent “general” mindsets across domains, except those in the Opposing profile, who combined a growth mindset for intelligence and creativity with a fixed mindset for giftedness. Students in the Opposing profile outperformed others in mathematics and foreign languages, while those in the Growth profile excelled across other subjects. The Fixed profile was linked to the lowest achievement, except in reading, foreign languages, and music, where Mixed and Fixed profiles performed similarly. Girls were more likely to belong to the Growth profile, while boys dominated the Fixed and Opposing profiles.DiscussionThe findings highlight the cross-domain nature of mindsets but reveal unique domain-specific variations, particularly for giftedness. These differences influenced academic outcomes, underscoring the nuanced role of mindsets in student achievement. Gender disparities in mindset profiles align with observed differences in school performance.ConclusionBy identifying distinct mindset profiles, this study emphasizes the complexity of students’ beliefs and possible educational implications. Future research should explore qualitative aspects of mindset formation across ability-related constructs, its broader motivational frameworks, and their relation to students’ academic outcomes.